2015
DOI: 10.1371/journal.pone.0117795
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Testicular Corticosterone Biosynthesis in Adult Male Rats

Abstract: Corticosterone is synthesized in the adrenal glands and is circulated throughout the body to perform regulatory functions in various tissues. The testis is known to synthesize and secrete testosterone and other androgens. We developed an accurate method to measure steroid content using liquid chromatography-mass spectrometry analysis. In the present study, significant levels of the precursor compounds of testosterone and corticosterone synthesis could be detected in rat testis using this method. After adrenale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
(36 reference statements)
1
11
0
2
Order By: Relevance
“…Of note, even after adrenalectomy, corticosterone concentrations in testicular IF remained higher than in the serum. These findings, supported by a previous study, indicate the possibility that corticosterone could be produced intratesticularly . More detailed recent analysis revealed that, among the testicular cells, TM are the principal source of corticosterone production in the male gonad .…”
Section: The Microenvironment Determines the Phenotype Of Tmsupporting
confidence: 80%
“…Of note, even after adrenalectomy, corticosterone concentrations in testicular IF remained higher than in the serum. These findings, supported by a previous study, indicate the possibility that corticosterone could be produced intratesticularly . More detailed recent analysis revealed that, among the testicular cells, TM are the principal source of corticosterone production in the male gonad .…”
Section: The Microenvironment Determines the Phenotype Of Tmsupporting
confidence: 80%
“…Pre-clinical data have shown that acute stress might impair testicular function; testicular tissue from stressed rats shows higher levels of cortisol displayed apoptosis of both germ cells and Leydig cells [ 14 , 15 ]. By contrast, the net effects of stress might be determined by chronic as demonstrated by the presence of glucocorticoid receptors (GRs) in Leydig, [ 16 ], Sertoli [ 17 ] and germs cells [ 15 ]; permanently high levels of glucocorticoid are believed to induce apoptosis of all cell types [ 15 17 ]. The Leydig cell is the primary target of glucocorticoid regulation in the testes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that TP can suppress corticosterone/cortisol synthesis and secretion in vivo and in vitro. Maeda et al found that corticosterone was involved in the regulation of glycolysis and spermatogenesis. Because TP (even at a dose of 50 μg/kg) not only induces decreases in sperm motility and effects on the epididymal structure in the testicles but also prolongs the estrous cycle and reduces the relative weights of the ovary and uterus, corticosteroids are likely potential biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty‐six female Wistar rats (aged 8‐10 weeks and weighing 180‐220 g) were purchased from Beijing Vital River Laboratory Animal Technology Co, Ltd (Beijing, China, License number: SCXK, Beijing, 2016‐0006), and housed at the Experimental Animal Center of China Pharmaceutical University under specific pathogen free (SPF) conditions with food and water provided ad libitum. The CIA model was established in half of the rats, and the induction and assessment of the CIA model were performed as previously described . Briefly, the Wistar rats were immunized with 200 µg of bovine type II collagen (Chondrex, Seattle, WA) emulsified in an equal volume of complete Freund's adjuvant (Sigma, Deisenhofen, Germany).…”
Section: Methodsmentioning
confidence: 99%